Rheological and structural characterization of emulsified modification bitumen synthesized from industrial waste - Mohd Najib, Razali (2020)
The cooler surface temperature than surrounding air may result in condensation which will propagate the growth of mould and fungi. This problem also occurs in the public health sector such as in the operation theatre of a hospital. The operation theatre has to maintain the temperature lower than the ambient condition which may result in condensation and lead to fungi problems. The aim of this study is to eradicate the fungi problems through coating and insulation by formulating Emulsified Modified Bitumen (EMB) using three types of emulsifier (anionic, cationic, and non-ionic). The industrial grade bitumen (60/70) will be modified with recycle used oil and mix with three different types of emulsifier producing three different formulated (EMB A, EMB B, and EMB C). In this research project, industrial waste such as recycle used oil was being used as other alternative to reduce the usage of raw bitumen in the formulation of EMB and also to reduce the excessive environmental issue in Malaysia. EMB A is using the anionic emulsifier, EMB B is using cationic emulsifier and EMB C is using nonionic emulsifier. The formulated EMB samples being analysed for their characterization and performance test on a dry wall substrate. From the analysis, EMB B shows the best performance among all three formulated EMB with the best characterization in terms of viscosity, rheological behaviour and flash point and also resulting in the fastest drying rate at 8 hours and good adhesiveness properties with no flaking occurs except for the emulsion stability, EMB A showing the best stability performance of only 1.69% water separated from the original volume of water. It can be concluded that in terms of characterization and performance, cationic emulsifier (EMB B) is the most suitable for EMB formulations for coating purpose meanwhile anionic emulsifier (EMB A) will contribute to the stability of emulsion. %. The accelerated, natural and cooling ageing period are 296days, 1107 days and 893days. The total heat transfer (q) at temperature of 60℃, 45℃, 30℃ and 27℃ are 1.14W, 0.79W, 0.70W and 0.65W. It can be concluded that the ageing period and insulation effect are directly proportional to the bitumen composition.